"Conocimientos y Práctica Sobre el AutoExamen de Mamas en Mujeres de Moche"-2011 - Sarmiento Pérez, Viviana Graciela
This research study, of type quantitative, descriptive and correlational was performed on Moche Pueblo on Moche community, in order to determine the relationship between the knowledge about self breast examination and the practice of this self breast examination in women among 15 and 60 years old. The sample universe was consisted of 135 women who met the inclusion criteria of the investigation. For data collection was used the instrument: structures survey of knowledge about self breast examination and the test of the practice of self breast examination. The information obtained was processed in SPSS 15.0 version and analyzed by statistical test “chi square”. The results are presented in tables of simple and double-entry, after analysis was obtained the following conclusions: 1. Of all the women in study concerning the level of knowledge about the breast examination the 5.9 percent have poor level information, while the 60.7 shows fair information and the 33.3 percent present a good level of knowledge. 2. Of the total of women the 64.4 percent practice poorly the self breast examination procedure and 35.6 percent fair practice. 3. There a high meaningful relationship among the level knowledge on the self breast examination and the practice of self breast examination. Keywords: level of knowledge, self breast examination, women and practice.